2011
DOI: 10.1371/journal.pone.0027014
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immediate and Sustained Memory Enhancing Effects of Alpha7 Nicotinic Receptor Agonists and Allosteric Modulators in Rats

Abstract: The α7 nicotinic acetylcholine receptor (nAChR) is a potential target for the treatment of cognitive deficits in patients with schizophrenia, ADHD and Alzheimer's disease. Here we test the hypothesis that upregulation of α7 nAChR levels underlies the enhanced and sustained procognitive effect of repeated administration of α7 nAChR agonists. We further compare the effect of agonists to that of α7 nAChR positive allosteric modulators (PAMs), which do not induce upregulation of the α7 nAChR. Using the social disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Callahan et al (2013) demonstrated that the combination of PNU-120596 (1-10 mg/kg) with a subthreshold dose of donepezil improved recognition memory. Moreover, the effects of CCMI (described as AVL-3288) on recognition memory were assessed in the social discrimination test in rats (Thomsen et al, 2011). In this study, the memory-enhancing effects of CCMI (1 mg/kg) were demonstrated at 24 h after repeated, but not single, administration.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
See 1 more Smart Citation
“…Callahan et al (2013) demonstrated that the combination of PNU-120596 (1-10 mg/kg) with a subthreshold dose of donepezil improved recognition memory. Moreover, the effects of CCMI (described as AVL-3288) on recognition memory were assessed in the social discrimination test in rats (Thomsen et al, 2011). In this study, the memory-enhancing effects of CCMI (1 mg/kg) were demonstrated at 24 h after repeated, but not single, administration.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
“…It cannot be excluded that repeated dosing protocols might reveal differences between these two types of α7-nAChR PAMs. For example, Thomsen et al (2011) demonstrated enhanced social cognition in rats after a 7-day administration of CCMI but not of PNU-120596.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…agonists can improve the performance of a variety of memory and attention tasks that depend on PFC circuits (30)(31)(32)(33). The study identifies the cellular basis for these behavioral actions, showing that stimulation of α7-nAChRs produces an inverted-U dose-response both for spatially tuned neuronal firing patterns and for behavioral performance, enhancing NMDAR-mediated neuronal representations of visual space.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent study is of particular interest showing that the a7 nAChR agonist A-582941 and the a7 nAChR PAM AVL-3288 increase short-term memory in rats 24 h after repeated, but not a single, administration, suggesting that it is repeated administration of both agonists and PAMs, i.e., chronic rather than acute dosing, which may produce sustained (e.g. neuroplastic) effects on cognitive performance (Thomsen et al, 2011). Needless to say that if one decides to conduct a chronic dosing trial as part of a proof-of-mechanism study, one would ideally use additional functional biomarkers (and not just P50 sensory gating) that are more closely related to the concept of neuroplasticity like transcranial magnetic stimulation (TMS)-elicited motor-evoked potential (MEP) amplitudes (Thirugnanasambandam et al, 2011).…”
Section: Discussionmentioning
confidence: 99%